The Influence of Facility Maintenance and Service Quality on Student Satisfaction on Trans Padang Bus Corridor 1 - Nasywa Farhanah Izan; Boni Saputra (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Bus Trans Padang Corridor 1 serves as a primary mode of public transportation for students in Padang City; however, social media observations from August to December 2025 revealed persistent complaints regarding facility conditions and service performance, indicating a gap between user expectations and perceived service delivery. This study examines the effects of facility maintenance and service quality on student satisfaction with Bus Trans Padang Corridor 1. A quantitative associative-causal design was employed, involving 97 junior and senior high school students selected through accidental sampling. Data were collected using a closed-ended questionnaire measured on a five-point Likert scale and analyzed through multiple linear regression using SPSS 20. The findings indicate that facility maintenance significantly affects student satisfaction (t = 9.067, p < .001, R² = .464), while service quality also exerts a significant effect (t = 12.879, p < .001, R² = .636). Simultaneously, facility maintenance and service quality significantly explain 66.6% of the variance in student satisfaction (F = 96.651, p < .001, adjusted R² = .666), as represented by the regression equation Y = −5.830 + 0.415X₁ + 0.492X₂. These findings support the Expectation-Disconfirmation Theory and are consistent with the P-Transqual and SERVQUAL frameworks, demonstrating that student satisfaction is shaped by both the physical reliability of transportation facilities and the quality of service delivery. The study contributes empirical evidence on student satisfaction in urban public transportation and underscores the need for Perumda PSM and the Padang City Transportation Agency to integrate facility maintenance and service-quality improvements to enhance the performance of Bus Trans Padang Corridor 1.